Skin expression of IL-23 drives the development of psoriasis and psoriatic arthritis in mice - Chen, Lili; Deshpande, Madhura; Grisotto, Marcos; Smaldini, Paola; Garcia, Roberto; He, Zhengxiang; Gulko, Percio S.; Lira, Sergio A.; Furtado, Glaucia C. (Scientific reports, 2020)
Psoriasis (PS) is a chronic skin inflammation. Up to 30% of the patients with PS develop psoriatic arthritis (PsA), a condition characterized by inflammatory arthritis that affects joints or entheses. Although there is mounting evidence for a critical role of interleukin-23 (IL-23) signaling in the pathogenesis of both PS and PsA, it remains unclear whether IL-23-induced skin inflammation drives joint disease. Here, we show that mice expressing increased levels of IL-23 in the skin ( K23 mice) develop a PS-like disease that is characterized by acanthosis, parakeratosis, hyperkeratosis, and inflammatory infiltrates in the dermis. Skin disease preceded development of PsA, including enthesitis, dactylitis, and bone destruction. The development of enthesitis and dactylitis was not due to high circulating levels of IL-23, as transgenic animals and controls had similar levels of this cytokine in circulation. IL-22, a downstream cytokine of IL-23, was highly increased in the serum of K23 mice. Although IL-22 deficiency did not affect skin disease development, IL-22 deficiency aggravated the PsA-like disease in K23 mice. Our results demonstrate a central role for skin expressed IL-23 in the initiation of PS and on pathogenic processes leading to PsA.